2017
DOI: 10.12688/f1000research.12887.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic susceptibility in wound infections: A pilot study from Bangladesh

Abstract: Introduction: Infections due to antibiotic resistant bacteria have increased alarmingly in both developed and developing countries. Unrestrained and rapidly spreading bacterial growth has turned the management of wound infections into a serious challenge. This study aimed to determine the prevalence of different bacterial pathogens and their antibiotic susceptibility in various types of wound infections. Methods:  A cross-sectional study was conducted to collect 105 wound swabs. All isolated bacteria were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
3
9
2
Order By: Relevance
“…Besides penicillin, other tested antibiotics showed some form of resistance (multidrug-resistant) against S. aureus which is similar to the findings of previous studies (Erami et al, 2014;Neyra et al, 2014;Chen et al, 2016;Roy et al, 2017;Anueyiagu et al, 2020). The lowest percentage of animal origin S. aureus were resistant to oxacillin and the lowest percentage of human origin S. aureus were resistant to fusidic acid.…”
Section: Discussionsupporting
confidence: 87%
“…Besides penicillin, other tested antibiotics showed some form of resistance (multidrug-resistant) against S. aureus which is similar to the findings of previous studies (Erami et al, 2014;Neyra et al, 2014;Chen et al, 2016;Roy et al, 2017;Anueyiagu et al, 2020). The lowest percentage of animal origin S. aureus were resistant to oxacillin and the lowest percentage of human origin S. aureus were resistant to fusidic acid.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are comparable with those of other published studies ( 16 , 17 ). In contrast, the outcome of this study contradicted with ( 18 ) study as the authors have reported that the Escherichia coli isolates showed sensitivity to cefixime, azithromycin, cefotaxime and ceftazidime. The difference can be explained by the fact that the isolation site as the cited study has isolated the Escherichia coli from wound infections whereas the current study from bottled water.…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, in previous work they were resistant to methicillin but all sensitive to Vancomycin (Javeed et al, 2011). Similarly Roy et al (2017) stated that 59.1% for cotrimoxazole and 66.2% resistant to tetracycline but in present study resistant to amoxicillin is 88.8% while resistant to ceftrizidime is 85%. Getachew et al (2018) reported that resistance of S. aureus to methicillin continuously increased day by day and also show multidrug resistant pattern against common antibiotics.…”
Section: Discussioncontrasting
confidence: 41%
“…Pus consists of a buildup of dead leukocytes (white blood cells) from the body's immune system in response to infection. Pus forming bacteria are called Pyogenic (Madigan and Martin, 2006 (Roy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%